Concurrent validation and reliability of the silhouette scale to assess body image in adolescents living in a high altitude region of Peru - Sanchez Macedo, Lucila; Fuentes-Lopez, Jose; Villegas-Abril, Claudia; Ayala-Pineda, Kelly (Nutrición Clínica y Dietética Hospitalaria, 2025)
Background: To verify the validity and reliability of the silhouette scale to assess self-perception of body image in adolescents living in a high altitude region. Methods: A descriptive cross-sectional study was designed in 1149 adolescents (366 males and 783 females) with an age range of 12 to 17 years from an altitude region of Peru. The actual weight and height of the adolescents were evaluated. Body mass index (BMI) and Tri-ponderal Index (TPI) were calculated. Body image was evaluated through the silhouette method proposed by Stunkard (scale from 1 to 9 silhouettes). Results: There was a moderate correlation between the silhouette scale and anthropometric indicators (BMI and TPI) in both sexes. In females it was (R= 0.52 to 0.56, p<0.000) and in males (R= 0.34 to 0.47, p<0.000). The limits of agreement of the Bland-Altman plot reflected a high degree of agreement between the measures (retest). The correlation coefficient of agreement in males was R=0.83. In females it was R= 0.90 and in both sexes it was R= 0.88. The mean differences in males were 0.18 points, in females 0.08 points and in both sexes 0.11 points. Conclusion: The Stunkard silhouette scale is valid and reliable to assess body image in adolescents of both sexes in a high altitude region of Peru. The results suggest its use and application in contexts where anthropometric equipment is lacking